Integration of Green Economy and Digital Marketing in the Empowerment of Coffee Farmers in Belatungan Village: Circular Economy Approach and Market Transformation - I Dewa Gede Kresna Wirawan; I Wayan Suanda; Putu Siti Firmani (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: Coffee farmers in Belatungan Village, Bali, face challenges, including low economic returns and environmental degradation due to inefficient waste management. The study aims to improve economic sustainability and environmental health by integrating the principles of circular economy and digital marketing. This intervention involves converting coffee husk waste into biochar and promoting digital marketing strategies to improve market access. Contribution: This study expands the market reach and income potential of farmers through digital marketing. This study contributes to rural economic development and environmental sustainability by implementing a circular economy model in agriculture while integrating digital tools for empowerment. Method: A Participatory Action Research (PAR) approach was used, involving farmers in the design, implementation, and evaluation of projects. The methodology includes technical training on biochar production, digital marketing, and ongoing mentoring. Results: The intervention successfully converted 80% of coffee husk waste into biochar, leading to a 15% increase in land productivity and a 25% reduction in chemical fertilizer usage. Additionally, digital marketing efforts, including e-commerce activation and eco-friendly packaging, resulted in a 20% increase in online sales and a 15-20% increase in farmers' income. Conclusion: The study successfully achieved its goal by integrating circular-economy practices with digital marketing, thereby improving economic and environmental outcomes for coffee farmers.